DESIGN AND FABRICATION OF ALTERNATIVE COOLING SYSTEM FOR CONVENTIONAL PURPOSE - N. Yogaraj; P. Ganeshan; P. Raju; P.A. Nigal Ashik; B. Boobalan; K. Arumugam; D. Dinesh Kumar; V. Logeshwaran; K. Raja (Pakistan Journal of Biotechnology, 2018)
The main purpose of this alternate cooling system is to circulate cooling air to the surrounding that means it will act as an air cooling system. Instead of using water, ice cubes are used here. The exhaust fan plays a main purpose of the exhaust fan is to suck the air from the closed area (polystyrene container) and supply to surrounding. The polystyrene box is nothing but the thermocol container and it is shaped into required dimensions for fitting the exhaust fan at the center of the box. The sufficient ice cubes are kept inside the box. Once the ice bars are filled into the closed container the vapour arises, after completing all the setting process the exhaust fan is switched to ON position, so that it exhausts the vapour to the surrounding. The cooling capacity is measured with the help of digital thermometer and the temperature is to be noted for every 2 hours so that the verification of the cooling capacity is to be done.